2017
DOI: 10.1097/bpb.0000000000000353
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for the treatment of simple bone cysts of the humerus: open curettage and bone grafting either without instrumentation or with intramedullary nailing

Abstract: Functional and radiographic outcomes, in addition to complication and reoperation rates of open curettage and grafting without instrumentation or with intramedullary nailing, in the treatment of simple bone cysts (SBCs) of the humerus were compared. Thirty-seven children [25 males, 12 females; median age=9.5 years (range, 3-17 years)] with humeral SBC were treated with curettage and grafting without instrumentation (group 1, 21 patients) or with intramedullary nailing (group 2, 16 patients). The pathological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The average age of onset is 8 to 14 years old. [15] Simple bone cysts mostly occur in males, and the male-to-female ratio is 2:1 to 4:1 [13,6,7] ; pain caused by intercurrent pathological fracture is often the first symptom, and 63% to 87% [1,3] of cysts are combined with pathological fracture before surgery. According to the Neer evaluation criterion, bone cysts can be divided into a latent stage and an active stage, in which the active stage accounts for 37.9% to 57.9%.…”
Section: Introductionmentioning
confidence: 99%
“…The average age of onset is 8 to 14 years old. [15] Simple bone cysts mostly occur in males, and the male-to-female ratio is 2:1 to 4:1 [13,6,7] ; pain caused by intercurrent pathological fracture is often the first symptom, and 63% to 87% [1,3] of cysts are combined with pathological fracture before surgery. According to the Neer evaluation criterion, bone cysts can be divided into a latent stage and an active stage, in which the active stage accounts for 37.9% to 57.9%.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the complications in this study proved that early operation, including curettage, bone graft and ESIN, could achieve the same results as a delayed operation. Erol et al 21 also reported that a very similar combination treatment of curettage, grafting and ESIN, achieved a high cure rate in humerus UBCs. The extended curettage and grafting stimulated bone formation and ESIN not only contributed to continuous drainage of the cyst but also provided stability to the pathological fractures.…”
Section: Discussionmentioning
confidence: 94%
“…The extended curettage and grafting stimulated bone formation and ESIN not only contributed to continuous drainage of the cyst but also provided stability to the pathological fractures. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone-replacement plastic surgery is traumatic and it is associated with long-term transplant restructuring and numerous complications such as shortening development, false joints, deformity and muscle wasting [15,16]. The current trend involves withdrawal of resection bone plastic surgery.…”
mentioning
confidence: 99%